2011
DOI: 10.1002/cncr.26291
|View full text |Cite
|
Sign up to set email alerts
|

Novel antagonists of growth hormone‐releasing hormone inhibit growth and vascularization of human experimental ovarian cancers

Abstract: BACKGROUND:Antagonists of growth hormone-releasing hormone (GHRH) inhibit the proliferation of various human cancer cell lines and experimental tumors by mechanisms that include direct action on GHRH receptors in cancer cells. METHODS: In this study, the effects of newly synthesized GHRH antagonists, MIA-313, MIA-602, MIA-604, and MIA-610, were investigated in 2 human ovarian epithelial adenocarcinoma cell lines, OVCAR-3 and SKOV-3, in vitro and in vivo. The expression of receptors for GHRH was demonstrated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 65 publications
3
30
0
Order By: Relevance
“…This finding can further support the theories that, on certain cancer cells and tumors, SV1 functions as the main therapeutic target, 32 and in melanomas has a crucial role in the progression of the disease. 22 The exposure of A375 cells to MIA-690 altered the subcellular localization of p27, an event that is, at least in part, responsible for the observed changes in cell cycle progression.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding can further support the theories that, on certain cancer cells and tumors, SV1 functions as the main therapeutic target, 32 and in melanomas has a crucial role in the progression of the disease. 22 The exposure of A375 cells to MIA-690 altered the subcellular localization of p27, an event that is, at least in part, responsible for the observed changes in cell cycle progression.…”
Section: Discussionsupporting
confidence: 83%
“…41,42 In the present study, after treatment with MIA-690, the mRNA level of IL-8 markedly dropped. Our laboratory has earlier shown that treatment with GHRH-antagonists inhibits growth and vascularization of experimental ovarian cancer via decreasing VEGF secretion, 32 suggesting that one of the cornerstones of the antitumor effect of GHRH-antagonists might be derived from its angiogenesis inhibiting potential.…”
Section: Discussionmentioning
confidence: 99%
“…tumor growth in vivo, we obtained GHRH antagonists with greatly increased antitumor activity, but with reduced GH and IGF-1 inhibiting activity (6,22). Thus, the main effect of latest GHRH antagonists such as MIA-602 is likely to be exerted by the suppression of the action of tumoral GHRH through the inhibition of its binding to GHRH-Rs, which results in decreased cell cycle progression as well as increased apoptosis (6,13,21,50).…”
Section: Discussionmentioning
confidence: 98%
“…GHRH antagonists were prepared in our laboratory by solid-phase synthesis using Boc chemistry and purified by reversed-phase HPLC as described previously (6,22,25 ]hGH-RH(1-29)NH2. Noncoded amino acids and acyl groups used in the peptides are abbreviated as follows: Abu, α-aminobutyric acid; Ada, 12-aminododecanoic acid; Agm, agmatine; Cpa, parachloro-phenylalanine; Fpa5, pentafluoro-phenylalanine; Har, homoarginine; Me-Ala, Nmethyl-alanine; Nle, norleucine; Orn, ornithine; PhAc, phenylacetyl; Try (Me), O-methyl-tyrosine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation